Genetic Variants in miRNAs Are Associated With Risk of Non-syndromic Tooth Agenesis - Gu, Min; Yu, Xin; Fan, Liwen; Zhu, Guirong; Yang, Fan; Lou, Shu; Ma, Lan; Pan, Yongchu; Wang, Lin (Frontiers in Physiology, 2020)
Non-syndromic tooth agenesis (NSTA) is one of the most common dental abnormalities. MiRNAs participated in the craniofacial and tooth development. Therefore, single nucleotide polymorphisms (SNPs) in miRNA genes may contribute to the susceptibility of non-syndromic tooth agenesis. Here, a total of 625 non-syndromic tooth agenesis cases and 1,144 healthy controls were recruited, and four miRNA SNPs (miR-146a/rs2910164, miR-196a2/rs11614913, pre-miR-605/rs2043556, pre-miR-618/rs2682818) were genotyped by the TaqMan platform. Rs2043556 showed nominal associations with risk of non-syndromic tooth agenesis (PAdd = 0.021) in the overall analysis, as well as upper lateral incisor agenesis (PAdd = 0.047) and lower incisor agenesis (PAdd = 0.049) in the subgroup analysis. Notably, its significant association with upper canine agenesis was observed (PAdd = 0.0016). Rs2043556 affected the mature of miR-605-3p and miR-605-5p while dual-luciferase report analysis indicated that MDM2 was the binding target of miR-605-5p. Our study indicated that pre-miR-605 rs2043556 was associated with risk of non-syndromic tooth agenesis.